A Zebrafish Embryo Behaves both as a "Cortical Shell – Liquid Core" Structure and a Homogeneous Solid when Experiencing Mechanical Forces. (26th September 2014) - Liu, Fei; Wu, Dan; Chen, Ken
Abstract Mechanical properties are vital for living cells, and various models have been developed to study the mechanical behavior of cells. However, there is debate regarding whether a cell behaves more similarly to a "cortical shell – liquid core" structure (membrane-like) or a homogeneous solid (cytoskeleton-like) when experiencing stress by mechanical forces. Unlike most experimental methods, which concern the small-strain deformation of a cell, we focused on the mechanical behavior of a cell undergoing small to large strain by conducting microinjection experiments on zebrafish embryo cells. The power law with order of 1.5 between the injection force and the injection distance indicates that the cell behaves as a homogenous solid at small-strain deformation. The linear relation between the rupture force and the microinjector radius suggests that the embryo behaves as membrane-like when subjected to large-strain deformation. We also discuss the possible reasons causing the debate by analyzing the mechanical properties of F-actin filaments.